The Role of the Drugs Unit in Implementing Counseling Guidance to Prevent Drug Abuse at Cimahi Police - Arbianto, Alkuba Ariftu (Police Studies Review, 2024)
The development of science and technology also influences the condition of social problems, one of which is drug abuse. Drug cases, especially in Cimahi Regional Police have increased. Narcotics Unit is a special unit at the Regional Police level which has the role of prevention through counselling guidance. The purpose of this study is to describe the role of the Narcotics Unit in preventing drug abuse through counselling guidance at the Cimahi Regional Police Station. This research uses a qualitative approach and type of field research. The focus of research is on preventing drug abuse through counselling guidance at the Cimahi Regional Police Station. The sources used are primary sources obtained from interviews, secondary sources obtained from study documents, and observations made related to the type of research. Triangulation techniques are used in testing the validity of the data. Data analysis by reducing data and presented relevant data, so that conclusions can be determined. The findings obtained are the number of Narcotics Unit personnel carrying out the counselling guidance function only four people. Personnel have not mastered communication because they have never attended vocational education. It is necessary to organize personnel in an orderly manner and discussion among members to improve their literacy. The intensity of the task implementation of the Narcotics Unit is passive due to the absence of a budget. The Narcotics Unit has not yet played a role because of incomplete infrastructure facilities such as communication tools, transportation, and instruction tools for giving guidance. Conduct joint activities and complete infrastructure for carrying out tasks. The method of giving counselling guidance is not yet on target because it is more waiting for invitations to give counselling guidance. The absence of official agreement with other agencies so that the activities and objectives of the cooperation carried out are unclear. Cooperation must be done in officially in various fields.